Low-Dose and Standard Overnight and Low Dose-Two Day Dexamethasone Suppression Tests in Patients with Mild and/or Episodic Hypercortisolism - Mojtahedzadeh, Mona; Shaesteh, Nesyah; Haykani, Mastaneh; Tran, Jennifer L. A.; Mangubat, Michael; Shahinian, Hraya K.; Nachnani, Rahul; Zopey, Mohan; Saidian, Jason; Thomas, Antolice; Lee, Martin L.; McCutcheon, Ian E.; Friedman, Theodore C. (Hormone and Metabolic Research, 2018)
We previously reported on the lack of utility of the 1 mg overnight dexamethasone (DEX) test in mild and/or periodic Cushing’s syndrome, as most patients with the condition suppressed to 1 mg DEX. It is possible that a lower dose of DEX as part of an overnight DEX test might be able to distinguish between mild and/or periodic Cushing’s syndrome and those without the condition. The objective of the current study is to determine the sensitivity and specificity of a 0.25 mg overnight DEX suppression test, the standard 1 mg overnight DEX suppression test, and the two-day low-dose (Liddle test) DEX suppression test with and without correction for DEX levels in patients evaluated for mild and/or periodic Cushing’s syndrome. Thirty patients determined to have Cushing’s syndrome by biochemical testing and 14 patients determined not to have the condition had the 0.25 mg and standard 1 mg overnight DEX suppression test and the two-day low-dose DEX suppression tests. Our results show that morning serum cortisol and cortisol/DEX ratios following an overnight dexamethasone suppression test were similar in patients with Cushing’s syndrome and those not having Cushing’s syndrome. However, a morning cortisol value above 7.6 μg/dl following a dose of DEX of 0.25 mg was found in 12 patients with Cushing’s syndrome and none in those not having Cushing’s syndrome, suggesting that a high cortisol value after this low dose of dexamethasone can indicate that further testing for Cushing’s syndrome is warranted. Our data suggest that the traditional 1 mg overnight or the 2 mg/2 day DEX suppression testing should no longer be used as a screening test in patients who could have mild and/or periodic Cushing’s syndrome, while the 0.25 mg dose of DEX may pick up some patients with mild Cushing’s syndrome.
Keywords: Cushing’s syndrome; cortisol; hypercortisolism; episodic; periodic